Corporate Criminal Liability for Workplace Accidents under Law Number 1 of 2023 - Wiransyah Syatha (Media Hukum Indonesia (MHI), 2026)
Workplace accidents remain a serious issue in industrial relations in Indonesia, particularly in the implementation of occupational safety and health standards that result in losses for workers. In practice, workplace accidents do not only involve individual responsibility, but may also give rise to corporate criminal liability as a legal subject. The regulation of corporate criminal liability has been strengthened through Law Number 1 of 2023 concerning the Criminal Code, which explicitly recognizes corporations as subjects of criminal law. The legal issues examined in this study include the form of corporate criminal liability for workplace accidents based on the element of negligence and the application of the element of negligence to corporations under Law Number 1 of 2023. This study employs a normative juridical research method with statutory and conceptual approaches. The legal materials used consist of primary legal materials in the form of legislation related to criminal law and labor law, as well as secondary legal materials including literature, scientific journals, and relevant legal doctrines. The analysis was conducted qualitatively to examine the concept of negligence and the construction of corporate criminal liability in workplace accident cases.